The Influence of Organizational Citizenship Behavior (OCB) and Leader-Member Exchange (LMX) on the SMEs Performance: How The Role of Organizational Commitment (OC) Mediation - Agus Susanto (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
The purpose of this study was to analyze the relationship between organizational citizenship behavior (OCB) and organizational commitment, to analyze the relationship between leader-member exchange and organizational commitment, to analyze the relationship between organizational citizenship behavior (OCB) and performance, to analyze the relationship between leader-member exchange and performance. analyze the relationship between organizational commitment variables and performance. In this study, the approach used by researchers is a quantitative approach. The respondents of this study were 230 UKM owners in Banten Indonesia. The data collection technique used by researchers is sampling with simple random sampling. The scale used in the research to fill in each question item uses a Likert scale with 5 (five) alternative answers, namely strongly agree (SS), agree (S), undecided (R), disagree (TS), strongly disagree ( STS). Data was obtained by distributing online questionnaires via social media. The approach taken when analyzing this research is the Structural Equation Model Partial Least Square (SEM-PLS) using SMART PLS software. In this study, the data analysis used was a validity test, a reliability test and a hypothesis test using SEM-PLS on 4 (four) variables. The formation of latent variables in this study are all reflective, which means that the four latent variables influence indicators. The results of this study are organizational citizenship behavior (OCB) has a positive and significant effect on organizational commitment, leader-member exchange has a positive and significant effect on organizational commitment, organizational Citizenship behavior (OCB) has a positive and significant effect on performance, leader-member exchange has a positive and significant effect on performance, organizational commitment has not significant significant effect on SMEs performance